2012
DOI: 10.1210/jc.2011-2994
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of 17β-Hydroxysteroid Dehydrogenase Type 1 Increases the Exposure of Endometrial Cancer to 17β-Estradiol

Abstract: Type 1 17β-HSD increases 17β-estradiol exposure in grade 1 EC, thus supporting tumor growth. This enzyme represents a potential therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 36 publications
6
72
1
Order By: Relevance
“…Interestingly, Cornel et al [37] reported significantly increased HSD17B2 mRNA levels only in G2 cancers versus control endometrium, while our data here show increased HSD17B2 expression in G1 cancers versus adjacent control endometrium. There were also significant differences in HSD17B2 expression in women with different menopausal status, where higher HSD17B2 mRNA levels were seen only in EC versus adjacent control endometrium for the post-menopausal patients.…”
Section: Gene Forward Primerscontrasting
confidence: 62%
“…Interestingly, Cornel et al [37] reported significantly increased HSD17B2 mRNA levels only in G2 cancers versus control endometrium, while our data here show increased HSD17B2 expression in G1 cancers versus adjacent control endometrium. There were also significant differences in HSD17B2 expression in women with different menopausal status, where higher HSD17B2 mRNA levels were seen only in EC versus adjacent control endometrium for the post-menopausal patients.…”
Section: Gene Forward Primerscontrasting
confidence: 62%
“…Increased expression of HSD17B1 has been reported in estrogen-dependent cancers [42][43][44][45]. Along with these findings, disturbances in the E2/E1 ratio, either in the plasma or in the tumor milieu, have been observed [44][45][46][47].…”
Section: Discussionmentioning
confidence: 94%
“…This further increases the local E2 concentration, leading to increased E2/E1 ratio in endometriosis lesions throughout the menstrual cycle [43,45,46]. Furthermore, in lowgrade endometrial carcinoma, HSD17B1 expression and activity are significantly increased without changes in P450 aromatase and HSD17B2 expression, hence, favoring E2 accumulation [47].…”
Section: Introductionmentioning
confidence: 99%